KEBIJAKAN LUAR NEGERI INDONESIA: TINJAUAN KRITIS TERHADAP HUBUNGAN BILATERAL DAN MULTILATERAL - Loso Judijanto; Melyana R Pugu; Al-Amin (CV. Adiba Aisha Amira, 2025)
Indonesia's foreign policy has shown diversity and dynamism, adjusting to changes in global and regional geopolitics. Strong bilateral relations with various countries and active participation in multilateral organisations such as ASEAN, the UN, and the G20 have raised Indonesia's economic and political profile in the world. A synergistic approach to political, economic and cultural diplomacy promotes national interests and contributes to global stability and prosperity. Nevertheless, Indonesia faces challenges in maintaining a balance between national interests and global demands, which requires a flexible and adaptive foreign policy. Going forward, the sustainability and eflectiveness of this policy will largely depend on adaptation and innovation eflorts to optimise Indonesia's role in the evolving world order.